Statistical analysis on application and funding of the National Natural Science Foundation of China in the area of information and communication systems, 2024 - HU Jie; ZHU Xiaojian; WEN Jun; SUN Ling (Tongxin xuebao)
The application and funding were statistically analyzed in the area of information and communication system in 2024, including general programs, young scientists funds, funds for less developed regions of National Natural Science Foundation of China (NSFC) in 2024. Detailed statistics were provided among different institutions, professional titles, research topics and keyword frequencies. Key programs were analyzed in terms of application and funding statistics as well as of different research topics in recent five years. Moreover, ages and professional titles of applicants for excellent young scientist funds and national science funds for distinguished young scholar were also revealed, while the impact of the relevant NSFC reforms in 2024 on scholar funds was also analyzed. Finally, major programs and young student funds were briefly introduced, in order to provide landscape of NSFC in the area of information and communication systems and offer references for scientists’ applications in 2025.